Bending Performance of Epoxy Adhesive Joints of Prefabricated Concrete Elements - Peng, Hongbo; Zhang, Zhongya; Zou, Yang; Guo, Jincen; Zhang, Xiaoyan; Zeng, Xingqi (Frontiers in Materials, 2022)
The assembly construction of prefabricated UHPC components can better balance quality reliability and construction convenience and have excellent bridge engineering application prospects. The joints between prefabricated components are the key to ensuring the overall force performance of the structure, which directly determines the load-bearing capacity and life of the structure. To clarify the bending behavior of epoxy adhesive joints between prefabricated UHPC components, four groups of 12 bending tests were carried out with different interface treatment forms as parameters. The failure modes, load-deflection curves, and ultimate bending strength of the interface were investigated. The test results reveal that the interfacial failure modes mainly include the interfacial stripping failure of epoxy-UHPC surface, steel fibers and fine aggregates into UHPC surface by pulling out, and tensile damage of UHPC at the root of key teeth on the side of the keyway interface. The load-deflection curves of all specimens exhibit the two-fold lines form. The load tends to rise linearly during the loading phase, and there is no yielding phase before the failure. The load-carrying capacity of the specimen is lost immediately after the failure, and no reliable residual strength is available except for the keyway interface. In addition, compared with the natural interface, the bending strength of rough interface, groove interface, and keyway interface are improved by -24.02%, 2.34%, and 4.64%, respectively, so it is recommended that the joint between prefabricated UHPC components take the form of keyway interface. Finally, an ABAQUS finite element model based on the traction-separation cohesive constitutive was established to verify the reliability of the experimental results. The deviation of interfacial ultimate bending strength is 3.67%, which indicates that the model can better predict the force behavior and ultimate bending strength of joints of epoxy adhesive prefabricated UHPC components.